The critical thinking skills and independent learning analysis: The flipped classroom based on blended learning - Ernawati Ernawati; A.S. Alonemarera; Tri Maniarta Sari (STKIP Persada Khatulistiwa Sintang, 2022)
The results of observations in the Biology Education Study Program of Sembilanbelas November Kolaka University, until now the lecture activities carried out in general still use the conventional model which causes students to tend to be passive, the low independence of student learning which hinders students' thinking skills. For this reason, an innovative lecture model is needed that can develop and improve students' critical thinking skills and independence. The purpose of this study was to determine the critical thinking skills and independent learning of students through the flipped classroom model based on blended learning. This research is a quasi-experimental research using one group pretest-posttest design. Data collection by tests and questionnaires. Data were analyzed descriptively quantitatively and one sample t test. The results showed that the value of critical thinking skills of paired samples t-test obtained a significance level (p) of 0.00 < 0.05. For independent learning as a whole, the results of the paired samples t-test obtained a significance level (p ) of 0.00 < 0.05. So it can be concluded that students' critical thinking skills and independence are better when applying the blended learning-based flipped classroom model.